New Single Asymmetric Error-Correcting Codes - Al-Bassam, Sulaiman (1997)
New single asymmetric error-correcting codes are proposed. These codes are better than existing codes when the code length n is greater than 10, except for n = 12 and n = 15 . In many cases one can construct a code C containing at least [2^n/n] codewords. It is known that a code with |C| >= [2^n/(n + 1)] can be easily obtained. It should be noted that the proposed codes for n = 12 and n = 15 are also the best known codes that can be explicitly constructed, since the best of the existing codes for these values of n are based on combinatorial arguments. Useful partitions of binary vectors are also presented.